Modeling the external sector of the Nigerian economy - Central Bank of Nigeria, Research Department (Abuja, Nigeria : Central Bank of Nigeria, 2013)
The study aims to build and estimate external sector model of the Nigerian economy which can serve as a veritable tool for assessing and making forecast of external sector indicators.
Includes bibliographical references.
oif 06/03/17
Loans
Keywords: Economic forecasting; Macroeconomic modeling; Macroeconomics; Nigeria